Niger : Poverty Reduction Strategy Paper; 2005 Status Report. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the 2005 Status Report on Poverty Reduction Strategy Paper (PRSP) on Niger. The report is based on an assessment of economic and financial performance and sectoral policy and strategy implementation in 2005. The findings reveal that implementation of the priority sectoral policies and strategies by the various line ministries has been affected to some extent not only by Niger's geopolitical environment but also by compliance with the economic and financial program agreed upon with the Bretton Woods institutions.